Implementasi Sistem Informasi HIPPAM Desa Kaligondo Berbasis Web dan Android - Suwardiyanto, Devit; Suardinata, I Wayan; Subono, Subono (Universitas Nusantara PGRI Kediri, 2024)
The Banyuwono Drinking Water User Population Association (HIPPAM) is one of the business units of the Gondowangi Village-Owned Enterprise (BUMDES) in Kaligondo Village, Genteng District, Banyuwangi. This business unit is tasked with managing water sources in the village and distributing them to residents' homes in order to meet basic water needs for various community needs. So far, Banyuwono HIPPAM managers have experienced problems in managing residents' payment data because payments are made through collection by the head of the Neighborhood Association (RT) by recording them on payment cards and then reporting them to HIPPAM managers. This method has several disadvantages, such as the data received by the manager is slow, not neat and at risk of being lost or damaged. Likewise in the processing, recapitulation and reporting related to billing, total income and so on. Service activities for the implementation of the HIPPAM Banyuwono web and android application were held to overcome this problem. The activity begins by collecting data on needs and supporting facilities that are already available. This data will be used to design the flow and application design. Next, the design is implemented into a web and Android application using the Laravel framework, Flutter and MySQL database. The resulting web and Android applications have been published via the page http://bumdesgondowangikaligondo.id. 91% of users consisting of 5 HIPPAM officers and 53 RT heads in Kaligondo Village expressed satisfaction with the function and comfort of the application. The results of socialization and training on application use for 5 HIPPAM officers also showed that the officers already understood how to use the application with an average application mastery score of 88.